Effects of dry cupping therapy on pain, dynamic balance and functional performance in young female with recreational runners chronic plantar fasciitis - Malik, S.; Anand, P.; Bhati, P.; Hussain, E. (Sport-Orthopädie - Sport-Traumatologie, 2022)
Summary Background: There is limited evidence available on the effects of dry cupping therapy on outcomes of pain, dynamic balance and functional performance in young female recreational runners chronic plantar fasciitis. Purpose: To investigate the effectiveness of dry cupping therapy on pain, dynamic balance and functional performance parameters in young female recreational runners with chronic plantar fasciitis. Method: Thirty female recreational runners with plantar fasciitis were recruited from outpatient department of SGT hospital. They were randomly divided into two equal groups: Dry cupping therapy (Experimental group n = 15) and Conventional therapy (Control group n = 15). The experimental group received dry cupping therapy along with the conventional treatment whereas the control group received conventional treatment alone for 4 weeks (3 days/week). Outcome variables such as pain (Numeric pain rating scale), dynamic balance (Star excursion balance test) and functional performance (Figure of eight hop test) were evaluated at baseline and after 4 weeks of study period. Appropriate statistical tests were performed to test hypothesis the study hypothesis. Results: Findings suggested a significant improvement in parameters of pain, dynamic balance and functional performance (p < 0.05). However, these improvements were found to be significantly greater (p< 0.05) with the addition of dry cupping therapy to the conventional treatment. Conclusion: Findings of the present study suggests that dry cupping therapy may be considered as an adjunct treatment method in addition to the conventional treatment in young female runners with chronic plantar fasciitis.